2024
DOI: 10.1242/dev.202392
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences of somatic polyploidy in development

Gabriella S. Darmasaputra,
Lotte M. van Rijnberk,
Matilde Galli

Abstract: Polyploid cells contain multiple genome copies and arise in many animal tissues as a regulated part of development. However, polyploid cells can also arise due to cell division failure, DNA damage or tissue damage. Although polyploidization is crucial for the integrity and function of many tissues, the cellular and tissue-wide consequences of polyploidy can be very diverse. Nonetheless, many polyploid cell types and tissues share a remarkable similarity in function, providing important information about the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 188 publications
0
2
0
Order By: Relevance
“…These events are developmentally programmed in many tissues, such as the insect salivary gland, mammalian liver, and plant leaf epidermis (Dej and Spradling, 1999; Roeder et al, 2012; Gentric and Desdouets, 2014). Several studies have shown that increased DNA content causally increases cell size (Unhavaithaya and Orr-Weaver, 2012; Hansson et al, 2020; Ma et al, 2022; Darmasaputra et al, 2024). Given this association between DNA content and cell size, polyploidization may enable an accompanied increase in biosynthetic capacity, but such a requirement has never been tested in vivo .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These events are developmentally programmed in many tissues, such as the insect salivary gland, mammalian liver, and plant leaf epidermis (Dej and Spradling, 1999; Roeder et al, 2012; Gentric and Desdouets, 2014). Several studies have shown that increased DNA content causally increases cell size (Unhavaithaya and Orr-Weaver, 2012; Hansson et al, 2020; Ma et al, 2022; Darmasaputra et al, 2024). Given this association between DNA content and cell size, polyploidization may enable an accompanied increase in biosynthetic capacity, but such a requirement has never been tested in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that increased DNA content causally increases cell size (Unhavaithaya and Orr-Weaver, 2012;Hansson et al, 2020;Ma et al, 2022;Darmasaputra et al, 2024). Given this association between DNA content and cell size, polyploidization may enable an accompanied increase in biosynthetic capacity, but such a requirement has never been tested in vivo.…”
Section: Introductionmentioning
confidence: 99%